Object-Oriented Programming in C++ - Lafore, Robert (Noida, India Pearson, 2017)
Begins with the basic principles of the C++ programming language and systematically introduces increasingly advanced topics while illustrating the OOP methodology. This work contains chapters each of which reflects the ANSI C++ standard and the examples mirror the practices and standards.
Include Bibliography and Index.
Keywords: Object-oriented programming (Computer science) -- C++ (Computer program language)